1994
DOI: 10.1037/1196-1961.48.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhibition of return on voluntary and visually guided saccades.

Abstract: Four experiments examined the effects of inhibition of return on endogenously generated and visually guided saccades. In Experiments 1-3, subjects responded to a peripheral target by making either a prosaccade (toward the target) or an antisaccade (toward the field opposite the target). Prior to the appearance of the target, one of the two equiprobable target locations was activated by presenting a peripheral precue (Experiments 1 and 2), or by executing an endogenous saccade in response to a central precue (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
99
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 24 publications
8
99
2
Order By: Relevance
“…At longer SOAs, we found the opposite pattern, where both head and saccade reaction times were longer for the congruent compared with the incongruent condition. This effect is known as inhibition of return (IOR) and is commonly measured as the relative difference between congruent and incongruent conditions (Abrams and Dobkin 1994a,b;Klein 2000;Maylor and Hockey 1985;Posner and Cohen 1984;Posner et al 1985;Rafal et al 1994;ReuterLorenz et al 1996;Tanaka and Shimojo 1996;Taylor and Klein 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At longer SOAs, we found the opposite pattern, where both head and saccade reaction times were longer for the congruent compared with the incongruent condition. This effect is known as inhibition of return (IOR) and is commonly measured as the relative difference between congruent and incongruent conditions (Abrams and Dobkin 1994a,b;Klein 2000;Maylor and Hockey 1985;Posner and Cohen 1984;Posner et al 1985;Rafal et al 1994;ReuterLorenz et al 1996;Tanaka and Shimojo 1996;Taylor and Klein 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The empirical basis of our belief comes from studies in which observers are required to generate antisaccades. These studies almost exclusively show that the inhibitory effect can only be measured when the cue and target are presented in the same location (Rafal, Egly, & Rhodes, 1994;Fecteau, Au, Armstrong, & Munoz, 2004). The theoretical basis lies in the proposal (e.g., Forbes & Klein, 1996) that observers must inhibit the reflexive oculomotor system in order to behave according to instructions in the antisaccade task, a proposal for which there is support at the single unit level (see Everling, Dorris, Klein, &Munoz, 1999 andIgnashchenkova, Dicke, Haarmeier, &Thier, 2004).…”
mentioning
confidence: 99%
“…When overt orienting is required, subsequent responding is biased against the location of the cue. As such, repeat stimulation of an input pathway is not required to observe the effect (see also Posner et al, 1985) which can be measured with stimuli in central vision requiring responses compatible with the location of the peripheral cue (Taylor & Klein, 2000;Rafal, Egly, & Rhodes, 1994). This effect is commonly referred to as motoric/decisional (Taylor & Klein, 2000), or as occurring nearer the output end of the processing continuum (Hilchey, Klein, & Ivanoff, 2012).…”
mentioning
confidence: 99%
“…For example, Tipper et al (1991) demonstrated that lOR can become associated with an object and may, in fact, move in accordance with its trajectory to a new location, apparently indicating the existence of separate "what" and "where" inhibitory mechanisms (see also Tipper et al, 1994). Rafal, Egly, and Rhodes (1994) proposed that these two components might operate independently; location-based lOR might act to create a motor bias against returning the eyes to a previously attended location, while objectbased lOR might act to reduce sensitivity to the object with which it is associated.…”
mentioning
confidence: 99%